Respostas
respondido por:
1
(-7)²+(1/13)²-2+1³²=
49 + (1/13)^-2 + 1
49 + 13^2 + 1
49+ 169 +1
219
loshermanosmine:
E o 1 ^32?
respondido por:
0
^ = expoente ok?
Pelo que eu entendi é assim (-7)^2 + (1/13)^-2 - 2^10 + 1^32 (1/13)^-2 =
(13/1) ^2
49 + 169 + 1024 + 1
218+1024+1
1242+1 = 1243
R= 1243
(Caso não tenha errado nada é assim
Pelo que eu entendi é assim (-7)^2 + (1/13)^-2 - 2^10 + 1^32 (1/13)^-2 =
(13/1) ^2
49 + 169 + 1024 + 1
218+1024+1
1242+1 = 1243
R= 1243
(Caso não tenha errado nada é assim
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás